2016
DOI: 10.2147/ppa.s119973
|View full text |Cite
|
Sign up to set email alerts
|

Association between addressing antiseizure drug side effects and patient-reported medication adherence in epilepsy

Abstract: Background and aimAdherence to treatment is a critical component of epilepsy management. This study examines whether addressing antiepileptic drug (AED) side effects at every visit is associated with increased patient-reported medication adherence.Patients and methodsThis study identified 243 adults with epilepsy who were seen at two academic outpatient neurology settings and had at least two visits over a 3-year period. Demographic and clinical characteristics were abstracted. Evidence that AED side effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Patients were also more encouraged to ask about their medications and to get more information about adverse effects. 24 Results of this study were also consistent with those reported by Moura et al 25 who evaluated the effect of education about AEDs adverse effects on adherence and concluded that, despite knowledge about the possible adverse effects of AEDs, it did not affect their reported adherence to medications.…”
Section: Discussionsupporting
confidence: 89%
“…Patients were also more encouraged to ask about their medications and to get more information about adverse effects. 24 Results of this study were also consistent with those reported by Moura et al 25 who evaluated the effect of education about AEDs adverse effects on adherence and concluded that, despite knowledge about the possible adverse effects of AEDs, it did not affect their reported adherence to medications.…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous studies [10,30,34], each item is coded 0 if the answer is "Yes" and 1 if "No". A score can range from 0 to 4.…”
Section: Definition Of Dependent Variablesmentioning
confidence: 99%
“…Most of the anti-epileptic drugs have a lot of untoward effects which sometimes force the patients to stop these on their own or skip the doses. It is understandable and also reported in the literature by Moura et al, that using multiple medications for control of seizures in an epileptic patient result in non-adherence and management strategy of combining the AEDs eventually becomes counter theraputic 19,20 . This association was supported by our study analysis and polypharmacy emerged as strong predictor of non-compliance among the epileptic patients.…”
Section: Discussionmentioning
confidence: 94%
“…Studies by Getnet et al, and Moura et al, in 2016 in have also produced similar results. Longer duration of illness whether treated or untreated can have direct and indirect effects on the body which can give rise to various problems including the compliance 9,20 .…”
Section: Discussionmentioning
confidence: 99%